Using the Five-Level NPC Inverter to Improve the FOC Control of the Asynchronous Machine - Mouna Es-Saadi; Mohamed Khafallah; Hamid Chaikhy (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
Many researches have been dedicated to develop the induction motor drive control strategy used on the railway traction applications. In this paper we propose to investigate and to improve the electric locomotives by using a Field Oriented Control (FOC) strategy of induction motor drive. This induction motor can be powered by a five-stage neutral point inverter controlled by sinusoidal pulse width modulation (SPWM) due to good quality for output voltage and The use of fast switches. Both conventional and improved locomotives are simulated in Matlab/Simulink and compared in open loop conditions   and closed loop conditions using IP controller, in term of torque response, current harmonic distortions and rotor speed response.